Impact of Endotracheal Intubation on Interventional Endoscopy Unit Efficiency Metrics at a Tertiary Academic Medical Center. (June 2016) - Perbtani, Yaseen B; Summerlee, Robert J; Yang, Dennis; An, Qi; Suarez, Alejandro; Williamson, Blair J; Shrode, Charles W; Gupte, Anand R; Chauhan, Shailendra S; Draganov, Peter V; Forsmark, Chris E; Chang, Myron; et al.
Abstract : OBJECTIVES: Measures for evaluating interventional endoscopy unit efficiency have not been adequately validated, especially in reference to the involvement of anesthesia services for endoscopy. Primary aim was to compare process measures/metrics of interventional endoscopy unit efficiency between intubated and non‐intubated patients. Secondary aim was to assess variables associated with the need for endotracheal intubation. METHODS: The prospectively collected endoscopy unit metrics database at UF Health was reviewed for procedures performed in the interventional endoscopy unit for 6 months. Parameters included hospital‐mandated metrics available from the database. RESULTS: A total of 1, 421 patients underwent 1, 635 interventional endoscopic procedures and 271/1, 421 patients (19.1%) were intubated. There was no significant difference between intubated and non‐intubated cohorts with respect to age, gender, BMI, ASA Score, Mallampati Score, or the Charlson Comorbidity Index. Patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) were more frequently intubated than those undergoing non‐ERCP procedures (41.3 vs. 12.4%, P <0.0001). Inpatients comprised 48.3% of all intubated patients, whereas only 29.2% of non‐intubated patients were inpatients ( P <0.0001). Most patients (159/271, 58.7%) were intubated per anesthesiologist preference. All process efficiency metrics were significantly prolonged in the intubated compared with the non‐intubated patient cohort, except the time interval between successive procedures. Multivariate analysis revealed that patients with an anesthesiologist who had performed a greater number of total endoscopic sedations were less likely to be intubated than patients with an anesthesiologist who had performed fewer total procedures ( P =0.0066). CONCLUSIONS: Endotracheal intubation negatively impacts efficiency metrics in an interventional endoscopy unit. Careful assessment for the need for intubation should be emphasized.